VIRTUE AND POLITICS: AN ARISTOTELIAN READING OF NICCOLÒ MACHIAVELLI. - Bielskis, Andrius (Problems / Problemos, 2011)
The paper discusses Niccolò Machiavelli's conception of virtue (virtú) and republican politics from the point of view of Aristotelian virtue ethics. Machiavelli's emphasis on civic virtue and the support of republican politics bear similarity to Aristotle's conception of politics. Against two competing interpretations of Machiavelli's legacy (the Cambridge contextual historians school and Joseph V. Femia), this paper argues that while Machiavelli moves away from the classical conception of aretē / virtus, he also, at the same time, shares with an Aristotelian practical philosophy the concept of the republican common good. Machiavelli's modified conception of classical virtus and his republican rhetoric allows us to interpret his position as proto-nationalist. Finally, this paper argues that Machiavelli's cynical advice and observations can be partly explained by the gap between the Renaissance education of studia humanitatis and the ruthlessness of Realpolitik.